Effect of a Moderate Fish lntake on Platelet Aggregation in Human Platelet-Rich Plasma - Houwelingen, A C v; Hennissen, A A H M; Verbeek-Schippersa, F; Simonsen, T; Kester, A D M; Hornstra, G (Thrombosis and Haemostasis, 1988)
This paper describes the results of an international study to investigate the effect of a reasonable amount of dietary fish on platelet aggregation in platelet-rich plasma (PRP) induced by collagen and thrombin. In Maastricht, Tiomsø, and Zeist two groups of healthy male volunteers were given a daily dietary supplement consisting of 135 g of canned mackerel paste (experimental group, n = 40) or meat paste (control group, n = 42) for a 6-week period. Compliance, calculated on the basis of the urinary excretion of lithium, added to the supplements, was about 80%. Platelet number in PRP decreased significantly in the fish group. Collagen-induced platelet aggregation in PRP differed widely between the three centres despite the attempt to use exactly the same conditions. Nonetheless, aggregation decreased significantly in the fish group. The mackerel effect on thrombin-induced aggregation was inconsistent.
Keywords: Fish; Diet; Compliance; Platelte aggregation; Platelte number; PRP; Collagen; Thrombin